Minat Belajar Siswa dengan Variasi Penggunaan Media Pembelajaran (Survey pada Siswa Jurusan Akuntansi di SMK Negeri 3 Bandung) - Leni Maryani; Veri Aryanto Sopiansah (JURNAL PETIK, 2019)
The purpose of this study was to determine (1) how perceptions of students about the variety of instructional media, (2) the effect of variations in the use of instructional media on student interest accounting department at SMK Negeri 3 Bandung. The method used is survey with a student sample of the accounting department at SMK Negeri 3 Bandung. Analysis of the data used is the analysis of the data verification through calculation of average (mean) score for solving the first problem. As for solving the problem are both used a simple linear regression analysis. Results of research on the variations of the use of learning media can be summed variety of instructional media usage "Very Good" and indicators of a questionnaire on perceptions it is best to use video media. Based on regression analysis indicated by the coefficient of determination R Square, it can be stated that this hypothesis can be accepted. This means that there are significant variations in the use of instructional media on student interest. If you have students who are likely to have the characteristics of a passive, teachers should use the media interesting and varied learning related to the subject matter to be delivered.Keywords: Variation Use of Media Education and Student Learning Interests